2014
DOI: 10.1007/s00213-014-3657-4
|View full text |Cite
|
Sign up to set email alerts
|

The antipsychotic-like effects in rodents of the positive allosteric modulator Lu AF21934 involve 5-HT1A receptor signaling: mechanistic studies

Abstract: RationaleDiverse preclinical studies suggest the potential therapeutic utility of the modulation of the glutamatergic system in brain via metabotropic glutamate (mGlu) receptors. Lu AF21934, a positive allosteric modulator of the mGlu4 receptor, was previously shown to reverse behavioral phenotypes in animal models thought to mimic positive, negative, and cognitive symptoms of schizophrenia.ObjectivesTo begin elucidating the brain circuitry involved in mGlu4 receptor pharmacology and add mechanistic support to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 53 publications
8
22
1
Order By: Relevance
“…The present study expands on our recent reports showing that the novel compounds stimulating mGlu 4 receptor, both orthosteric agonists and PAMs, exhibit antipsychotic-like activity in animal models, widely used to study antipsychotic-like activity of drugs [ 15 - 17 , 33 ]. Herein, we describe the activity of the agonist of group III mGlu receptors, LSP4-2022 [ 34 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The present study expands on our recent reports showing that the novel compounds stimulating mGlu 4 receptor, both orthosteric agonists and PAMs, exhibit antipsychotic-like activity in animal models, widely used to study antipsychotic-like activity of drugs [ 15 - 17 , 33 ]. Herein, we describe the activity of the agonist of group III mGlu receptors, LSP4-2022 [ 34 ].…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, the use of lower doses of the compounds may reduce the risk of adverse effects that are often associated with higher doses. In a series of our previous experiments, we suggested that the interaction between mGlu 4 and 5-HT 1A receptors may be a good antipsychotic target [ 16 , 33 ]. In the present study, we showed that the therapy based on the interaction between mGlu 4 and GABA B receptors may prove beneficial for patients with a predominance of positive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The basic assumption of the study was to establish if the administration of subeffective doses of the ligands of those receptors would exert antipsychotic-like activity without inducing adverse effects typical for standard dopamine-based antipsychotics. Such simultaneous action of the combined treatment was reported previously for subeffective doses of mGlu 4 -5-HT 1A receptor ligands (Wierońska et al 2013 , 2015 ). In addition, studies were undertaken with the combined administration of mGlu 4 and GABA B activators, but the efficacy of subeffective doses of the combination of these ligands was not evident in the models of negative and cognitive symptoms of schizophrenia, although the ligands exerted antipsychotic efficacy when active doses of each compound were administered alone (Wierońska et al 2015 ; Woźniak et al 2016 ).…”
Section: Introductionsupporting
confidence: 76%
“…The spatial delayed alternation test was performed using a wooden T-maze, according to Sławińska et al, 2013 and Wierońska et al, 2015b .…”
Section: Methodsmentioning
confidence: 99%